Getting into Shape: Limb Bone Strength in Perinatal Lemur catta and Propithecus coquereli. Issue 2 (23rd December 2018) - Young, Jesse W.; Jankord, Kathryn; Saunders, Marnie M.; Smith, Timothy D.
ABSTRACT: Functional studies of skeletal anatomy are predicated on the fundamental assumption that form will follow function. For instance, previous studies have shown that the femora of specialized leaping primates are more robust than those of more generalized primate quadrupeds. Are such differences solely a plastic response to differential loading patterns during postnatal life, or might they also reflect more canalized developmental mechanisms present at birth? Here, we show that perinatal Lemur catta, an arboreal/terrestrial quadruped, have less robust femora than perinatal Propithecus coquereli, a closely related species specialized for vertical clinging and leaping (a highly unusual locomotor mode in which the hindlimbs are used to launch the animal between vertical tree trunks). These results suggest that functional differences in long bone cross‐sectional dimensions are manifest at birth, belying simple interpretations of adult postcranial form as a direct record of loading patterns during postnatal life. Despite these significant differences in bone robusticity, we find that hindlimb bone mineralization, material properties, and measures of whole‐bone strength generally overlap in perinatal L. catta and P. coquereli, indicating little differentiation in postcranial maturity at birth despite known differences in the pace of craniodental development between the species. In a broader perspective, our results likely reflect evolution acting during prenatal ontogeny. Even though primates are notable for relatively prolonged gestation and postnatal parental care, neonates are not buffered from selection, perhaps especially in the unpredictable and volatile environment of Madagascar. Anat Rec, 2018. © 2018 Wiley Periodicals, Inc. Anat Rec, 303:250–264, 2020. © 2018 American Association for Anatomy